2020
DOI: 10.1007/s00146-020-00998-w
|View full text |Cite
|
Sign up to set email alerts
|

Children’s perceptions of social robots: a study of the robots Pepper, AV1 and Tessa at Norwegian research fairs

Abstract: This article studies perceptual differences of three social robots by elementary school children of ages 6–13 years (n = 107) at research fairs. The autonomous humanoid robot Pepper, an advanced social robot primarily designed as a personal assistant with movement and mobility, is compared to the teleoperated AV1 robot—designed to help elementary school children who cannot attend school to have a telepresence through the robot—and the flowerpot robot Tessa, used in the eWare system as an avatar for a home sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The children also perceived a robot as being a companion. These findings tell us that the social imaginary of a robot from a child's perspective is guided, as pointed out by Søraa and colleagues, by an emotional connection with the robot, rather than by a rationally driven notion of the robot's usefulness [15]. Our results are also consistent with [16], who found that from a child's perspective robots are entities with which children can form social relationships.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The children also perceived a robot as being a companion. These findings tell us that the social imaginary of a robot from a child's perspective is guided, as pointed out by Søraa and colleagues, by an emotional connection with the robot, rather than by a rationally driven notion of the robot's usefulness [15]. Our results are also consistent with [16], who found that from a child's perspective robots are entities with which children can form social relationships.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that access to high-quality education is limited in rural settings [33], that family income in urban settings is significantly higher than in rural families, and that the level of education is 56% lower for rural men and 49% for rural women than that for people living in cities [34]. Another explanation for the technical details provided by the children in the urban setting might be what Søraa and colleagues [15] called "technological determinism." How a child imagines what a robot is and does is based on learned experience predetermined by exposure to existing robots.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that it was a tablet, a physical object, made it an artifact with which people started to talk in their native language. This affectionate reaction is achieved with such artifacts, rather than with apps (35). Apparently, including an avatar that invoked culturally positive meanings facilitated the creation of such an affectionate relationship as well.…”
Section: Technology In the Lives Of Older Adultsmentioning
confidence: 98%